The principle of legality: An approximation from the social state of law - Orbegoso Silva, Miluska (2020)
This investigation will carry out a study of the Principle of Legality in the Social State of Law, in which a criticism is made of the classic formulation of the same and a new understanding is proposed per the requirements that follow from the social clause and which affect the new Lending Public Administration. An understanding of the principle of legality is also raised based on the rule of law, but which responds to the new role played by the Lending Public Administration. It starts with a classic approach to it, a critique and finally a current approach to it.